Respons Peserta Didik Terhadap Penerapan Metode Diskusi Berbantu Google Classroom (Studi Kasus pada Pendidikan Agama Hindu di SD Fajar Harapan) - I Putu Suyasa Ariputra; Kadek Dwi Sentana Putra; I Nyoman Sumerta (Jurnal Penjaminan Mutu, 2022)
Following the Presidential Decree Number 12, 2020, the minister of education and culture of the Republic of Indonesia issued Circular Number 4, 2020 concerning the implementation of educational policies in the emergency period of the spread of Coronavirus Desiase (Covid-19) which instructed several things, one of which is the learning process carried out from home online or remotely. Google Classroom can be used to create and manage classes in a simple way, which makes this feature chosen by many educators to accommodate their learning. Based on preliminary observations on Hindu religious education and Character in grade IV SD Fajar Harapan leads to the discussion method, where students read the material provided by the educator then continue with a discussion in the message column available on the Google Classroom feature and occasionally use Google Meet. The purpose of this study was to determine the responsse of students to the discussion method applied in the Google Classroom in Hindu religious education learning and character. This study uses a questionnaire with Google Form in retrieving student impression data on the Google Classroom assisted lecture method. The questionnaire as a data collection method and a way of scoring on the questionnaire uses the linkert scale model. The responsse of grade IV students to the application of the Google Classroom-assisted discussion method in learning Hindu Religion and Character Education is of sufficient value based on the linkert scale table. This sufficient value is in the range of 42.8% which is in sufficient criteria which leads to weak criteria so that this method needs to be developed in order to increase the responsse and effectiveness of student learning in Hindu Religion and Character Education subjects.